God can wait: new migrants in Germany between early adaptation and religious reorganization - Diehl, Claudia; Koenig, Matthias (International migration, 2013)
We analyse migration-related changes in religiosity among new Polish and Turkish migrants in Germany by using data from an international project on Socio-Cultural Integration Processes of New Immigrants in Europe (SCIP). The study confirms that after migration, both groups experience a decrease in religious practices that is more pronounced among Muslim Turks than among Catholic Poles and more pertinent for worship attendance than for prayer. Among new Polish immigrants, religious decrease is greater for individuals with stronger social ties to the secular German mainstream and there are no signs that religious practices are resumed after the disruptive first couple of months. For Turks, however, our study shows that initial religious decrease is followed by a process of religious reorganization, independent of social assimilation. We discuss the role that “bright” symbolic boundaries against Islam may play in explaining these group-specific patterns.
Gesehen am 01.06.2021
Keywords: Deutschland